Pengaruh Kualitas Layanan terhadap Kepatuhan Membayar Pajak - Albari Albari (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2009)
The study is to examine the effect of service quality and satisfaction of the tax compliance of taxpayers to pay taxes. It is the case study in Yogyakarta Branch of Tax Office. In the study the concept of quality of service tax office and taxpayers satisfaction based on five dimension including reliability, assurance, responsiveness, empathy, and tangible. The research data was obtained with 191 respondents involves taxpayers in the two branches of the tax office in Yogyakarta by taking a sample of convenience sampling. With the data processing program Amos, was obtained the result that service quality had a positive effect on adherence indirectly through a variable of satisfaction. While based on Wilcoxon analysis concluded that some quality assessment items, service and taxpayer satisfaction are empirically proven to different.Keywords: Service quality, satisfaction, compliance, taxpayers, and service dimensions